2020
DOI: 10.5194/acp-2020-903
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of reduced anthropogenic emissions during COVID-19 on air quality in India

Abstract: Abstract. To mitigate the impacts of the pandemic of coronavirus disease 2019 (COVID-19), the Indian government implemented lockdown measures on March 24, 2020, which prohibit unnecessary anthropogenic activities and thus leading to a significant reduction in emissions. To investigate the impacts of this lockdown measures on air quality in India, we used the Community Multi-Scale Air Quality (CMAQ) model to estimate the changes of key air pollutants. From pre-lockdown to lockdown periods, improved air quality … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…Overall, N AIT reduced by approximately 85% during LCD, implying reduced primary anthropogenic emissions or secondary formation or both. The time evolution of number concentrations of N TOT also showed similar reductions (86%) during LCD (Figure 4b), indicating that the air quality was significantly improved due to the primary emission reduction during LCD (Srivastava et al., 2021; Zhang et al., 2021).…”
Section: Resultsmentioning
confidence: 66%
“…Overall, N AIT reduced by approximately 85% during LCD, implying reduced primary anthropogenic emissions or secondary formation or both. The time evolution of number concentrations of N TOT also showed similar reductions (86%) during LCD (Figure 4b), indicating that the air quality was significantly improved due to the primary emission reduction during LCD (Srivastava et al., 2021; Zhang et al., 2021).…”
Section: Resultsmentioning
confidence: 66%
“…For instance, the pandemic restrictions in most of the European countries occurs in parallel with exceptionally blue skies and new extremes in surface irradiance ( van Heerwaarden et al, 2021 ). Improved air quality associated with COVID-19 lockdowns were also documented for India ( Srivastava et al, 2021 , Zhang et al, 2021 ), Iran ( Broomandi et al, 2020 ), and the United States ( Berman and Ebisu, 2020 ).
Fig.
…”
Section: Introductionmentioning
confidence: 87%
“…In addition to major urban agglomerations, the study on Hat Yai, Thailand, indicated that small cities also saw air quality improvements during the lockdown period ( Stratoulias and Nuthammachot, 2020 ). As a heavily polluted country, India experienced unprecedented air pollutant emission decline during the pandemic ( Das et al, 2021 ; Sharma et al, 2020 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%